Mutation in The Nuclear‐Encoded Mitochondrial Isoleucyl–tRNA Synthetase IARS2 in Patients with Cataracts, Growth Hormone Deficiency with Short Stature, Partial Sensorineural Deafness, and Peripheral Neuropathy or with Leigh Syndrome. Issue 11 (18th October 2014) - Schwartzentruber, Jeremy; Buhas, Daniela; Majewski, Jacek; Sasarman, Florin; Papillon‐Cavanagh, Simon; Thiffaut, Isabelle; Sheldon, Katherine M.; Massicotte, Christine; Patry, Lysanne; Simon, Mariella; Zare, Amir S.; McKernan, Kevin J.; et al.
<x xml:space="preserve">Abstract</x> Growth chart of CAGSSS proband ages 2 to 18 years. Genetic target height is estimated from parents. Proband is far below 5th percentile for both height and weight. A short course of growth hormone was given at age 16, with a modest but clearresponse in height. Age of menarche was typical. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>